Frequency of Current Smokers and Ex-Smokers among Patients of Pulmonary Tuberculosis (Medical Forum Monthly, 2024)
Objective: To document and investigate the frequency of current smokers and ex-smokers among patients of pulmonary tuberculosis.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Pulmonology, Nishtar hospital, Multan from November 2016 to April 2017.Materials and Methods: A total number of 151 (100%) patients were enrolled in the study. SPSS version 23 was used to analyze patient’s data, Mean and standard deviation was calculated for quantitative data and frequency (percentages) was calculated for qualitative data like gender and smoking status. Chi square test was applied to see effect modification, p value ≤ 0.05 was considered as significant.Results: A total number of 100% (n=151) patients were diagnosed with pulmonary tuberculosis included in this study. The main outcome variable of this study was smoking status (current smoker or ex-smoker). Out of 100% (n=151) patients, in our study, it was observed that 62.9% (n=95) were current smokers and 37.1% (n= 56) were ex-smokers.Conclusion: Smoking has strong correlation withpulmonary tuberculosis and pretreatment positive smear. Smokers had more than a 5-fold increased risk of a pretreatment positive smear than non-smokers which is significant number, indicating markable effects of smoking on the risk of TB transmission.